Phenomenological Modeling And Classical Control Of A Pneumatic Muscle Actuator System - Sakthi Velu, Vasanthan; Chong, Shin Horng; Tan, Ming Hui; Md Ghazaly, Mariam (Science And Engineering Research Support Society (SERSC), 2016)
This paper focuses on the parameter characterization of phenomenological modelling for commercially available Festo Fluidic Muscle Actuator. Phenomenological model consists of a spring element, nonlinear damping element and a contractile force element which arranged in parallel. The dynamic model was tested on the experimental setup which allows precise and accurate contraction due to the supply of pressure (P) to the PMA. The open loop data were collected for static load study and contraction study at several constant pressures. Only the contraction experiment was focused in this study by excluding the relaxation phase of the experiment. The result obtained shows that at constant pressure, the muscle actuator behaves like a spring and a nonlinear damping element. The contractile force coefficient element is the corresponding force generated by the muscle during contraction in longitudinal direction. Since, pressure is the main driving element in PMA system, all the coefficient value has a pressure dependent relationship. The model and parameters obtained from the study were further validated by predicting the contraction of the muscle system via simulation and experimental. Then, a classical PID control system was designed and validated in point-to-point positioning motion experimentally. Finally, a brief conclusion of the pneumatic muscle actuator experimental setup and dynamic system modeling is made.